Respostas

2014-01-29T13:41:54-02:00
   7  +  1
   2      2       =
   2  -  1
   5     2

mmc (2, 5) = 10

       8
       2          =
   4  -  5 
      10 

4 ÷ (- ) =
        10

4 * (- 10) = 4 * (- 10) = - 40
         1
-----------------------------------------------------------------------------------------------------------------

    7  +  1
    2      3         =
    3   -  2
            3    

mmc (2, 3) = 6
 mmc (1, 3) = 3 

     21  +  2
          6               =
      9  -  2        
          3

     23   ÷   7 =
      6         3 

23  *  3  =  
 6      7
69 =  1   9   ou  23
42         14       14